2018
DOI: 10.1016/j.memsci.2018.05.077
|View full text |Cite
|
Sign up to set email alerts
|

Effect of salinity and nanoparticle polydispersity on UF membrane retention fouling

Abstract: In this study, the retention potential and the fouling of ultrafiltration (UF) multichannel hollow fiber membrane regarding nanoparticles (NPs) have been assessed. Filtration experiments of fluorescent 10 nm and 1.5 nm NPs (respectively NP-10 and NP-1.5) suspensions filtered individually were carried out under different transmembrane pressures. A complexification of the feed suspension through the mix of NPs sizes and/or the salinity adding have been investigated. The retention rate (RR), the fouling location … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“…In addition to these studies of viral vector purification, a number of investigators have looked at the ultrafiltration of model nanoparticles that may be significant environmental toxins. For example, Le Hir et al [ 16 ] evaluated the effects of salinity and polydispersity on the ultrafiltration of small (1.5 and 10 nm) nanoparticles and noted significant effects of intermolecular interactions between the nanoparticles and with the membrane. Jassby et al [ 17 ] examined the filtration of C60 fullerenes in the presence of different salts, showing that the addition of divalent cations led to the formation of large aggregates that were more highly retained by a ceramic membrane.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to these studies of viral vector purification, a number of investigators have looked at the ultrafiltration of model nanoparticles that may be significant environmental toxins. For example, Le Hir et al [ 16 ] evaluated the effects of salinity and polydispersity on the ultrafiltration of small (1.5 and 10 nm) nanoparticles and noted significant effects of intermolecular interactions between the nanoparticles and with the membrane. Jassby et al [ 17 ] examined the filtration of C60 fullerenes in the presence of different salts, showing that the addition of divalent cations led to the formation of large aggregates that were more highly retained by a ceramic membrane.…”
Section: Introductionmentioning
confidence: 99%
“…Off-line CLSM membrane characterization has also been used by Gao et al [45] in an attempt to understand the mechanisms governing the adsorption of organic matter on aged polyvinylidene fluoride (PVDF) membranes. In a more recent study, CLSM has has been used to characterize the retention of nanoparticles (1.5 and 10 nm) by UF PES hollow-fiber membranes [46].…”
Section: Confocal Laser Scanning Microscopymentioning
confidence: 99%
“…Synthetic nanoparticles have been increasingly utilized as model particles in process optimization studies. This approach enables researchers to investigate and optimize various parameters, such as buffer and surfactant concentrations, for enhanced viral vector-like nanoparticle throughput . Several investigators have considered the use of model particles as contaminants in water treatment applications. , In earlier work, done by Chu et al, the retention of 30 nm polystyrene nanoparticle suspensions was investigated as a model for AAV3 . Moreover, a recent study investigating single pass tangential flow filtration of 100 nm nanoparticles indicated they are a good model for lentivirus .…”
Section: Introductionmentioning
confidence: 99%
“…28 Several investigators have considered the use of model particles as contaminants in water treatment applications. 29,30 In earlier work, done by Chu et al, the retention of 30 nm polystyrene nanoparticle suspensions was investigated as a model for AAV3. 28 Moreover, a recent study investigating single pass tangential flow filtration of 100 nm nanoparticles indicated they are a good model for lentivirus.…”
Section: Introductionmentioning
confidence: 99%